Career adaptability, resilience, and life satisfaction: A mediational analysis in a sample of parents of children with mild intellectual disability†. Issue 4 (2nd October 2018) - Ginevra, Maria Cristina; Di Maggio, Ilaria; Santilli, Sara; Sgaramella, Teresa Maria; Nota, Laura; Soresi, Salvatore
ABSTRACT: Background: Parents of children with intellectual disability (ID) have been found to be more likely to experience lower levels of life satisfaction than parents of typically developing children as a result of the increased challenges they experience. Based on a life design approach, which emphasises the role of career adaptability and resilience in dealing with life challenges, this study aimed at analysing the relationship between career adaptability and life satisfaction through the mediational role of resilience in parents of children with mild ID. Method: One hundred and fifty-two (62 fathers and 90 mothers) parents of children with mild ID were involved and were administered measures of life satisfaction, career adaptability, and resilience. Results: The structural equation model showed that career adaptability is indirectly, through resilience, related to life satisfaction. Conclusion: This result has important implications for practice, and it underscores the need to support parents' life satisfaction, promoting their resilience, and especially their career adaptability.